Pengaruh fisioterapi dada terhadap perubahan respirasi rate pada pasien dengan gangguan pernafasan - Prayoga, Andes; Furqoni, Prima Dian; Mz, Dennti Kurniasih (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: The prevalence of ARI in Lampung, according to the 2018 Basic Health Research (Riskesdas), was 7.38%. The highest incidence rates were in West Lampung Regency (12.67%), East Lampung (12.02%), and North Lampung (10.31%). Meanwhile, at Bintang Amin Hospital in Bandar Lampung in 2024, there were 102 ARI cases between June and December. Purpose: To determine the effect of chest physiotherapy on changes in respiratory rate in patients with respiratory disorders. Method: This quantitative study used a pre-experimental research design with a one-group pretest-posttest approach. The sample size for respiratory disorders at Bintang Amin Husada Hospital in Bandar Lampung in 2025 was 20 respondents, using purposive sampling. Univariate and bivariate data analysis used t-tests. Results: The average respiratory rate in patients with respiratory disorders before receiving chest physiotherapy was 29.05, while after receiving chest physiotherapy, the mean was 21.25. Bivariate data analysis using a t-test yielded a p-value of 0.000 < 0.05. Conclusion: Chest physiotherapy has an effect on changes in respiratory rate in patients with respiratory disorders. Keywords: Chest Physiotherapy; Respiratory Disorders; Respiratory Rates. Pendahuluan: Prevalensi kejadian ISPA di Lampung menurut Riskesdas 2018 yaitu 7.38%. Daerah tertinggi kejadian ISPA ada di Kabupaten Lampung Barat (12.67%), Lampung Timur (12.02%), dan Lampung Utara (10.31%). Sedangkan di RS Bintang Amin Bandar Lampung than 2024, kejadian ISPA sebanyak 102 pasien pada periode Juni s.d Desember. Tujuan: Untuk mengetahui pengaruh fisioterapi dada terhadap perubahan respirasi rate pada pasien gangguan pernafasan. Metode: Jenis penelitian kuantitatif menggunakan desain penelitian metode Pra Eksperimental dengan pendekatan one group pretes-postes design. Sampel gangguan pernafasan di Rumah Sakit Bintang Amin Husada Bandar Lampung Tahun 2025 dengan jumlah sampel minimal sebesar 20 responden dengan menggunakan teknik sampling purposive sampling. Analisa data univariat dan bivariat menggunakan uji t-test. Hasil: Rata-rata respirasi rate pada pasien gangguan pernafasan sebelum diberi fisioterapi dada di dengan mean 29.05 sesudah diberi fisioterapi dada dengan mean 21.25. Hasil analisa data bivariat menggunakan uji t-test didapat nilai p-value 0.000 < 0.05. Simpulan: Terdapat pengaruh fisioterapi dada terhadap perubahan respirasi rate pada pasien gangguan pernafasan. Kata Kunci: Fisioterapi Dada; Gangguan Pernafasan; Respirasi Rates.